Effects of the Stony Coral Tissue Loss Disease Outbreak on Coral Communities and the Benthic Composition of Cozumel Reefs - Estrada-Saldívar, Nuria; Quiroga-García, Blanca A.; Pérez-Cervantes, Esmeralda; Rivera-Garibay, Omar O.; Alvarez-Filip, Lorenzo (Frontiers in Marine Science, 2021)
In the Caribbean, disease outbreaks have emerged as significant drivers of coral mortality. Stony Coral Tissue Loss Disease (SCTLD) is a novel white plague-type disease that was first reported off the Florida coast in 2014. This disease affects >20 coral species and is spreading rapidly throughout the Caribbean. In December 2018, SCTLD reached southwestern (SW) Cozumel, one of the healthiest reef systems in the Caribbean. In this study, we integrate data from multiple survey protocols conducted between July 2018 and April 2020 to track the progression of the outbreak in SW Cozumel and to quantify the impacts of SCTLD on coral communities and the benthic composition of reefs. Given that the SCTLD outbreak coincided with a period of prolonged thermal stress that concluded in widespread coral bleaching in autumn 2019, we also investigated whether this event further exacerbated coral mortality. Our findings show that SCTLD spread throughout SW Cozumel in only 2 months and reached a peak after only 5 months. By the summer of 2019, most of the afflicted corals were already dead. Species of the families Meandrinidae, Faviinae, and Montastraeidae showed 33–95% mortality. The widespread coral die-off caused an overall loss of 46% in coral cover followed by a rapid increase of algae cover across all surveyed reefs that persisted until at least April 2020. In November 2019, more than 15% of surveyed coral colonies were bleached. However, we did not find that bleaching further increased coral mortality at either the colony or the community level, which suggests that the coral communities were able to recover from this event despite still being affected by the disease. In conclusion, SCTLD is radically changing the ecology of coral reefs by decimating the populations of several key reef-builders and reconfiguring the benthic assemblages. The actions needed to restore coral populations have to be accompanied by stringent controls related to the effects of climate change, coastal development, and wastewater treatment to improve coral conditions and ecosystem resilience.